Lower extremity stiffness in collegiate distance runners pre- and post-competition - Tavernite, J. P.; Moran, M. F. (Journal of Human Kinetics, 2020)
Previous evidence has suggested that there is a relationship between leg stiffness and improved running performance. The purpose of this investigation was to determine how leg stiffness of runners was influenced in the 24 and 48 hour period following a cross country race. Twenty-two collegiate cross-country runners (13 males, 9 females, 19.5 ± 1.4 yr) were recruited and participated in the study. Leg stiffness was assessed 24 hours before and after a race as well as 48 hours post-race. Three jumping protocols were conducted: 1) a static jump, 2) a countermovement jump, and 3) a vertical hopping test. Two embedded force plates (1000 Hz) were utilized to measure ground reaction forces for each test and a metronome was utilized to maintain hopping frequency (2.2 Hz). A significant main effect was found for a static jump, a countermovement jump and leg stiffness. Leg stiffness was significantly reduced 24 hours post-race (pre-race 36.84 kN·m-1, 24h post 33.11 kN·m-1, p < 0.05), but not 48 hours post-race (36.30 kN·m-1). No significant differences were found in post-hoc analysis for the squat jump, countermovement jump height and the eccentric utilization ratio. Following a cross-country race, leg stiffness significantly declined in a group of collegiate runners in the immediate 24 hours post-race, but returned to baseline 48 hours post-race. Sport scientists and running coaches may be able to monitor leg stiffness as a metric to properly prescribe training regiments.